Tingkat Hotel Bintang 5 Di Kota Bandung Dalam Menghadapi Bahaya Kebakaran - Lukman Subangi; Ketty Andayani; Ryan Gilang Wicaksono (DPPM Universitas Pelita Bangsa, 2022)
Hotel is a public facility where one of the elements that determine the image of the tourism product. Fire building is a problem that arises in a large city that is dense, so that the safety factor becomes very important. Therefore, the technical requirements of the building in the face of fire is very necessary as the reliability of the building, in addition to providing evacuation time and the arrival of the fire truck. This study aims to identify the readiness of building hotels in the face of a fire hazard. This study used a descriptive observational method, in which the research is a parameter measuring instrument reliability assessment of the fire protection of the three literature. Reliability assessment of fire protection can know the percentage of the total value of the sum of the percentage of component reliability owned fire protection. The results showed the condition of the reliability of buildings in the city of Bandung in less degree, do not fit at all or is at a dangerous level of fire safety. In improving the readiness of needed improvement, both on the part of building owners, building users, and government to reduce the risk of fire hazards. Keywords: Hotel, Fire, Reability, Readiness, Fire Protection